Management of a Caudolateral Radial Head Luxation in a five-month-old Shih Tzu - Langley-Hobbs, S. J.; Carmichael, S. (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
A caudolateral radial head luxation and concurrent distal humeroulnar subluxation were diagnosed in the left forelimb of a five-month-old Shih Tzu. The problems were treated successfully by proximal ulna osteotomy, reduction of the radial head luxation and placement of a transarticular external skeletal fixator (TESF). Three weeks postoperatively the reduction of the radial head luxation had been successfully maintained, the humero-ulnar luxation had corrected and the fixator was removed. There was a full range of motion in the left elbow joint and the radial head could not be reluxated.A caudolateral left radial head luxation in a five-month-old Shih Tzu was treated by ulna osteotomy, reduction of the luxation and placement of a transarticular external skeletal fixator. A concurrent humero-ulnar subluxation suggested that the problem was developmental, associated with premature closure of the distal ulnar growth plate in a chondrodys-trophic breed.
Keywords: Elbow; developmental; radial; luxation; chondrodystrophic; transarticular; external skeletal fixation